Exterior Warning Signals for Silent Buses - Berg, Karl; Hägglund, Ida (My University, 2016)
Electrical buses are manufactured in order to address issues with the global environment. The silent propulsion of electrical buses can be seen as a positive side effect as noise in the urban environment is reduced. However, concerns are raised as the silent buses may be harder to detect for a VRU, abbreviated Vulnerable Road User. This concern is addressed in pending legislation, pushing for technical solutions such as AVAS (Acoustical Vehicle Alerting System), which proposes addition of artificial sounds. We state questions of how warning signals could be designed in order to maintain effectiveness and comfortability, how well legislation requirements are met, and finally, a investigation of multi-modality. The warning signals to be designed are partly forced by pending legislation and partly desired from Volvo Buses, which give rise to potential shifts in priority and desired outcome. Action design research suits the change in scope that our efforts induced in the project, through conducting the project. The action design research suits a iterative design cycle in which each iteration results in prototypes that are evaluated provided a context in which it should operate within. The design perspective used in this project are inclusive and human centred design. The problem of detection isn't a novelty for many user groups in our society, why inclusive design was utilised. The use of human centred design is complementing the vast technical knowledge within Volvo Buses and provides an alternative perspective more suitable to subjective measurement. The design process includes four iterations, where each iteration has a divergence, transformation and convergence part. Meeting numerous experts, interviewees and users resulted in the Use Cases and User Scenarios. By identifying common patterns a model for warning signal design was formulated. The concepts were designed through a series of creative sessions and a workshop. Photography and video recording was used extensively in order to provide context and inspiration for design. The results consists of a designed Pattern-Event-Pattern (PEP) model for design of warning signals. The model consists of a pattern and events which can be utilised for designing warning signals that are effective and comfortable. The model is used to generate four design concepts: Eco, Care, Express and EWAS. The latter stands for Exterior Warning and Attention Signal and includes user evaluated audio warning signals. All concepts are described in respective video prototypes. Using multi-modality might be beneficial but remains to be tested. A comparison of visual and audio signals shows that the audio signals are dominant in respect to the visual signals. The dominance of audio signals is inherited as only secondary information can be found through the visual input. Our finding is that it's possible to design warning signals that receives high arousal and acceptable comfort in a Self Assessment Mannequin-scale evaluation. As the SAMscale evaluation provided context through a video prototype, due to time and ethical constraints, it remains to evaluate the warning signals in a real traffic situation. The suggested audio warning signals are mapped to a urgency rank which enables a coherent experience. The suggestions of audio signals excludes sounds that were super uous, already given by mechanical movement or dangerous to change.
Keywords: Människa-datorinteraktion (interaktionsdesign); Human Computer Interaction